2011
DOI: 10.4061/2011/762634
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury: Controversies Revisited

Abstract: This paper addresses the epidemiology of AKI specifically in relation to recent changes in AKI classification and revisits the controversies regarding the timing of initiation of dialysis and the use of peritoneal dialysis as a renal replacement therapy for AKI. In summary, the new RIFLE/AKIN classifications of AKI have facilitated more uniform diagnosis of AKI and clinically significant risk stratification. Regardless, the issue of timing of dialysis initiation still remains unanswered and warrants further ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 141 publications
(188 reference statements)
1
30
0
5
Order By: Relevance
“…Peritoneal dialysis was not used, consistent with previous experience (37). The most common RRT indication was hyperkalemia (69%), followed by azotemia (51%), volume overload (49%), and acidosis (45%).…”
Section: Discussionsupporting
confidence: 65%
“…Peritoneal dialysis was not used, consistent with previous experience (37). The most common RRT indication was hyperkalemia (69%), followed by azotemia (51%), volume overload (49%), and acidosis (45%).…”
Section: Discussionsupporting
confidence: 65%
“…1 The use of CM has risen in recent years due to an increase in radiographic procedures, and this coupled with an aging population already suffering from diabetes and cardiovascular/renal diseases (including chronic kidney disease, hypertension, hypotension, advanced congestive heart failure, and compromised left ventricular performance) has led to an increase in the incidence of CI-AKI. [2][3][4][5][6][7][8] CI-AKI…”
Section: Introductionmentioning
confidence: 99%
“…These are important factors in resource-poor areas where reliable power sources, access to clean water and water treatment plants might not be widely available 7. PD also carries a low bleeding risk and may be more suitable for some patients in terms of cardiovascular stability 3. Another advantage of PD is the absence of an extracorporeal circuit, which for our case was a key factor in view of our patient's religious beliefs.…”
Section: Discussionmentioning
confidence: 87%
“…The prospective multinational study carried out by Uchino et al 4 revealed that 5–6% of AKI on ICU required RRT, and this figure was consistent across the 23 participating countries. In the developed world, extracorporeal modes of dialysis, namely continuous RRT and intermittent haemodialysis, are the most commonly used forms of RRT in AKI, while acute PD is often overlooked 2 3. On the other hand, in the developing world, use of acute PD is more widespread 5 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation